An Analysis of Illocutionary Act in Movie Script of Frozen II - Ranal Rein; Sony Junaedi (LINGUAMEDIA Journal, 2022)
This study analyzes the types and function of illocutionary act in movie script of Frozen II. The approach in this study is pragmatic focusing on illocutionary act based on Searle. The writer found that many dialogues in movie script of Frozen II contains illocutionary act. In this study, the writer uses a qualitative method. Qualitative method is an analysis method based on data in the form of text. In this study, the writer found that there are five types of illocutionary acts contained in the movie script of Frozen II: 10 dialogues for representative illocutionary act, 8 dialogues for commissive illocutionary act, 9 dialogues for directive illocutionary act, 7 dialogues for expressive illocutionary act, and 2 dialogues for declaration illocutionary act. each type of illocutionary act in the script movie has a different function. Keywords: pragmatic, illocutionary act, qualitative, types, Frozen II